Historical institutionalism in Indonesia’s REDD+ climate policy: navigating the interplay between forest and climate governance institutions - Apriwan (Penerbit UKM, 2024)
This paper examines the relevance of ‘path dependence’ in Indonesia’s climate governance, particularly in Reducing Emissions from Deforestation and Forest Degradation (REDD+). This paper employs a conceptual model based on historical institutionalism, which explains the role of institutional structures and processes and the importance of critical junctures in reshaping them. This study explains how specific past events and practices shape institutions and their role in managing REDD+ climate policy in Indonesia. This study maps the development of Indonesia’s REDD+ programs during Indonesia’s democratic transition, highlighting its impact on forest governance reform. This paper argues that the institutional transformation of forest institutions creates institutionalized obstacles to the process of REDD+ implementation. The findings suggest that the interplay between forest and climate policy (REDD+) institutions reflects power asymmetries and leads to institutional continuity (re-equilibrium) and discontinuity of forest and climate institutions respectively